2017
DOI: 10.1371/journal.pone.0188028
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Syndrome: Promoting Independence and Return to Employment (InS:PIRE). Early evaluation of a complex intervention

Abstract: BackgroundMany patients suffer significant physical, social and psychological problems in the months and years following critical care discharge. At present, there is minimal evidence of any effective interventions to support this patient group following hospital discharge. The aim of this project was to understand the impact of a complex intervention for ICU survivors.MethodsQuality improvement project conducted between September 2014 and June 2016, enrolling 49 selected patients from one ICU in Scotland. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…Therefore, our results regarding self-efficacy were inconclusive. 28 However, it is clear that we did not achieve a difference in depressive symptoms between the study groups, as was found with a previous motivational interviewing face-to-face intervention. 3 All participants improved their scores for self-efficacy, depression, and fear of partner over time.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, our results regarding self-efficacy were inconclusive. 28 However, it is clear that we did not achieve a difference in depressive symptoms between the study groups, as was found with a previous motivational interviewing face-to-face intervention. 3 All participants improved their scores for self-efficacy, depression, and fear of partner over time.…”
Section: Discussionmentioning
confidence: 51%
“…Data were collected between September 2014 and June 2015. Complementary data from the InS:PIRE programme has been published elsewhere (10)(11)(12).…”
Section: Patientsmentioning
confidence: 99%
“…InS:PIRE, which runs on a cohort basis, aims to provide individualized health and social care resources, which patients and their caregivers need to make a safe and effective recovery. This program has been piloted in one site thus far and has demonstrated a signal of improved quality of life for the participants involved (69)(70).…”
Section: Health and Social Integrationmentioning
confidence: 99%